2015
DOI: 10.1007/s10551-015-2808-9
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Citizenship Behaviors of Directors: An Integrated Framework of Director Role-Identity and Boardroom Structure

Abstract: While directors' task boundaries are usually ambiguous, some of their activities or behaviors clearly constitute their formal duties, whereas others are usually perceived as organization citizenship behavior (OCB). Applying identity theory, we present a theoretical model that demonstrates one of the key drivers for directors to engage in OCB with a focus on their role identity. We argue that an individual director's role identity is one of the key factors that motivate directors to engage in OCB. Furthermore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Among others, it has been found that employee engagement in OCBs may increase knowledge sharing and job performance [23,24]. Other authors claim that OCBs exhibited by workers enhance team and group cohesiveness and contribute to overall organizational performance [2,23,[25][26][27]. At the same time, OCB does not mean working long hours and taking on extra assignments with no thought of reward.…”
Section: Organizational Citizenship Behaviormentioning
confidence: 99%
“…Among others, it has been found that employee engagement in OCBs may increase knowledge sharing and job performance [23,24]. Other authors claim that OCBs exhibited by workers enhance team and group cohesiveness and contribute to overall organizational performance [2,23,[25][26][27]. At the same time, OCB does not mean working long hours and taking on extra assignments with no thought of reward.…”
Section: Organizational Citizenship Behaviormentioning
confidence: 99%
“…As the apex of the decision-making process, the board must be equipped with appropriate human capital to effectively perform its oversight function (Forbes & Milliken 1999;Hambrick et al 2015;Hillman & Dalziel 2003;Yoshikawa & Hu 2017). As an outside director, government officials on board may have difficulties grasping the overall board discussions, which may involve specific knowledge such as SOE-related knowledge (e.g., the establishment acts, SOE and industry-related current issues, and financial and account systems), as they have limited time spent on the board tasks compared to their full-time job in the office (Hambrick et al, 2015;Kim et al 2014;Kor & Sundaramurthy 2009).…”
Section: Human Capital Of the Board Of Directorsmentioning
confidence: 99%
“…Previous research has found that corporate board members who had higher levels of identification engaged in more OCBs than those with lower levels of identification. (Yoshikawa & Hu, 2017).…”
Section: Supplemental Analysismentioning
confidence: 99%